The islamic law perspective on bequests to heirs in Gampong Pulo Pueb in Aceh, Indonesia - Asrul Sani; Alimuddin Alimuddin; Yusnaidi Kamaruzzaman (Jurnal Geuthèë: Penelitian Multidisiplin, 2026)
In Islamic law, a bequest (waṣiyyah) is fundamentally intended for non-heirs, as the rights of heirs have been explicitly determined through the rules of faraidh. However, in social practice, bequests to heirs are still commonly carried out based on considerations of custom, fairness, and family harmony. This study aims to analyze the practice of bequests to heirs in Gampong Pulo Pueb, Bandar Baru District, Pidie Jaya Regency, and to examine these practices from the perspective of Islamic law. This research employs an empirical juridical approach using a descriptive qualitative method. Data were collected through in-depth interviews with village officials, testators, and heirs, and analyzed descriptively. The findings indicate that bequests to heirs in Gampong Pulo Pueb are conducted both orally and in written form and are strongly influenced by local customs and family values. In some cases, bequests lead to disputes due to the absence of formal legal requirements, while in other cases they are implemented smoothly because they are supported by witnesses and the consent of all heirs. From the perspective of Islamic law, bequests to heirs are generally invalid, but may be implemented if all heirs approve them after the death of the testator (bil-idhin). Therefore, bequest practices that fulfill Islamic legal requirements and are based on family deliberation are consistent with the principles of justice, family harmony, and maqāṣid al-sharī‘ah.